2020
DOI: 10.1101/2020.07.07.192757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel evolution of UbiA superfamily proteins into aromaticO-prenyltransferases in plants

Abstract: AbstractPlants produce approximately 300 aromatic molecules enzymatically linked to prenyl side chains via C-O bonds. These O-prenylated aromatics have been found in taxonomically distant plant taxa as compounds beneficial or detrimental to human health, with O-prenyl moieties often playing crucial roles in their biological activities. To date, however, no plant gene encoding an aromatic O-prenyltr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…For the first round of screening, the candidate aromatic acceptors (1-20) were individually co-cultured with the recombinant S. cerevisiae strains correspondingly harbouring the empty pESC-HIS vector (negative control), MePT1, ΔTP-MePT1, MePT2, and ΔTP-MePT2, the metabolites in the yeast cells and culture media were extracted and carefully analysed by LC-MS. The feeding experiments revealed that MePT1 could only utilize the coumarins 1 and 2, among the twenty selected substrates (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), to generate unknown products with a molecular weight increased 136 Daltons which corresponds to the molecular weight of a geranyl chain. Surprisingly, MePT2 could not accept coumarins (1-8) as prenyl acceptors, even though the phylogenic analysis (Fig.…”
Section: Papermentioning
confidence: 99%
See 3 more Smart Citations
“…For the first round of screening, the candidate aromatic acceptors (1-20) were individually co-cultured with the recombinant S. cerevisiae strains correspondingly harbouring the empty pESC-HIS vector (negative control), MePT1, ΔTP-MePT1, MePT2, and ΔTP-MePT2, the metabolites in the yeast cells and culture media were extracted and carefully analysed by LC-MS. The feeding experiments revealed that MePT1 could only utilize the coumarins 1 and 2, among the twenty selected substrates (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), to generate unknown products with a molecular weight increased 136 Daltons which corresponds to the molecular weight of a geranyl chain. Surprisingly, MePT2 could not accept coumarins (1-8) as prenyl acceptors, even though the phylogenic analysis (Fig.…”
Section: Papermentioning
confidence: 99%
“…To analyse the catalytic potential of the candidate prenyltransferases, the recombinant yeast strains harboring the individual candidate gene were grown with 1 mM MgCl 2 and 0.1 mM aromatic acceptors (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in synthetic galactose media lacking histidine (SG-His) for 48 h (30 °C, 200 rpm). The cultures and cells were extracted by EtOAc (containing 10% methanol), and the organic layer was combined and concentrated under vacuum.…”
Section: Substrate Feeding Experimentsmentioning
confidence: 99%
See 2 more Smart Citations